ANALISIS AKTIVITAS ANTIOKSIDAN PRODUK SIRUP BUAH MENGKUDU (Morinda citrifolia L.) DENGAN METODE DPPH - Rahmawati Rahmawati; A. Muflihunna; Laode Muhammad Sarif (Jurnal Fitofarmaka Indonesia, 2015)
This research is about antioxidant activity analysis of Noni products syrup (Morinda citrifolia L.) using DPPH (1,1-diphenyl-2-picrylhydrazil) method. The research aimed to analysis of antioxidant activity of two different brands of Noni products syrup using spectrophotometer UV-Vis. This analysis using quarcetin as standard to determine antioxidant activity and DPPH reagen as radical sources. Quarcetin and  Noni products syrup are made five series concentrations in metanol. One ml of each concentration added 4 ml DPPH 50 µM and then added metanol up to 10 ml in flask. Then incubated for 30 minutes at room temperature and protected from light. Measurement of absorbance using spectrophotometer UV-Vis at 514 nm. The IC50 values were 25.7 µg/mL for brand A, and 9.839 µg/mL for brand B.